(Re)tratos da infância na primeira república no Brasil - Pinheiro, Larissa Franco de Mello Aquino (2023)
The scenario of this study has as reference the First Republic in Brazil (1889-1930), a period in which legislation reveals, the in its content, the concern around a social and political reordering with the emergence of republican ideals that dominated the country from that moment. The insertion of the school assumes a prominent role through action strategies on the inhabited space, including in the sense of an education with a disciplining character of children9s bodies to adapt to the project of modernity through some strategies such as the new school disciplines. Moreover, there was a medical-hygienist discourse by the authorities of the time that the streets are considered the place of idleness, immorality, and crime, being thus considered inappropriate to the presence of children. However, through available images it is possible to identify that the plane where the children are located allows other possibilities of reflection little evidenced in the studies about the children in the events of the city. Therefore, the aim of this investigation is to identify through photographs how children appropriate the spaces of the city, expressing a complex network of sociabilities and (dis)belonging in urban scenarios shared among different generational categories. The methodology is divided into bibliographic study and documentary research, especially analysis of photographs. The final considerations indicate that, through the different forms of sociabilities identified, the children live beyond the existing coexistence in school and in the domestic environment and that their presence in the city also represents forms of resistance to the normative frameworks of the republican disciplinary city.